The impact of socio-emotional wealth on the internationalization of Moroccan family businesses - (:unkn) unknown (My University, 2023)
The concept of the family firm has long attracted the interest of researchers and practitioners onseveral fronts: the governance of family firms, the profile of the leader, financing, transmissionand finally the behavior of these firms internationally. The objective of this thesis is to support theexistence of a positive relationship between socio-emotional wealth and the internationalization offamily businesses.Our research work highlights the relationship between socio-emotional wealth and theinternationalization of family businesses in the Moroccan context by relying on a contextualizationapproach of the measurement scales of the SEMR through the consideration of three dimensions:identification of family members with the business, emotional attachment, and the durability ofsocial ties through succession. We relied on a rich literature devoted to the internationalization offamily businesses and socio-emotional wealth to answer our problem and formulate our researchhypotheses.The choice of the Moroccan family business as a field of investigation is explained by severalreasons:- First, the participation of family businesses in the development of the Moroccan economy;- Secondly, the internationalization trend of Moroccan family businesses towards partner countriesin Morocco (West Africa, Europe, Central Africa, etc.);- The creation of several logistic platforms aligned to international standards;- The establishment of large international groups in Morocco, which has allowed Moroccancompanies to align with international standards and understand the culture of internationalization.The empirical results calculated on the basis of a sample of 51 Moroccan family firms show theexistence of a positive relationship between the durability of family ties through succession andthe choice of full control of the subsidiary to the detriment of shared control. Emotional attachmenthas a positive impact on the creation of the subsidiary. However, the identification of f
Keywords: African Research